2020
DOI: 10.37052/kanun.32(1)no7
|View full text |Cite
|
Sign up to set email alerts
|

Sejarah Kewujudan Golongan Kanak-Kanak Jalanan dan Definisi dalam Konteks Perundangan Malaysia

Abstract: AbstrakMenurut sejarah, kanak-kanak jalanan ialah golongan yang wujud hasil daripada perkembangan teknologi secara pesat, sehingga menyebabkan berlakunya penghijrahan masyarakat dari kawasan pedalaman ke bandar besar. Namun demikian, atas beberapa faktor yang menggagalkan usaha untuk menaik taraf kehidupan mereka, akhirnya wujud golongan kanakkanak jalanan. Sehingga kini, isu kanak-kanak jalanan masih menemui jalan buntu. Selain masalah yang dihadapi oleh mereka dari aspek ekonomi, sosial dan persekitaran, hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Meanwhile, to determine whether a person, boy or girl, can be criminally responsible or not, they must reach the latest 15 years according to Shafi'e and Hanbali schools (25)(26)(27). Meanwhile, Maliki and Hanafi School of thought except Abu Yusof, who agreed with the opinion of Shafi'e, in view that the age is up to 18 years old (27)(28). It may be concluded that the age of puberty and obligation followed by the age of criminal responsibility of children from Quranic perspective is based on a few criteria.…”
Section: Criminal Responsibility Of Children Under the Shari'ah Lawmentioning
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, to determine whether a person, boy or girl, can be criminally responsible or not, they must reach the latest 15 years according to Shafi'e and Hanbali schools (25)(26)(27). Meanwhile, Maliki and Hanafi School of thought except Abu Yusof, who agreed with the opinion of Shafi'e, in view that the age is up to 18 years old (27)(28). It may be concluded that the age of puberty and obligation followed by the age of criminal responsibility of children from Quranic perspective is based on a few criteria.…”
Section: Criminal Responsibility Of Children Under the Shari'ah Lawmentioning
confidence: 90%
“…It is noted that, the discussion on the children's exemption of criminal responsibility are referred particularly to the serious crimes fall under the categories of retaliation (Qisas) and Hudud punishment. (22,28) This is because, in other types of crime or civil liabilities, the children or in some cases, parents, can still be held liable and be made responsible (for example to pay Diyat(compensation)) in order to deter them from doing similar delinquent act in the future. The punishment of this kind may be considered Taazir (punishment other than Hudud) as a mean of educating (Ta'dib) rather than retribution (29).…”
Section: Criminal Responsibility Of Children Under the Shari'ah Lawmentioning
confidence: 99%
“…This paper concentrates on the study of Arts and Creativity intervention proposal in education for street children in Malaysia (Ab Rahman and Mat Basir 2020). The main area of discussion is on (i) the street children's basic needs, characteristics and holistic approach via arts and creativity in education especially in Kinaesthetic learning methods and (ii) how structured as well as thematic analysis that was conducted guides to led to a better learning environment through Kinaesthetic learning in education for the children of the street.…”
Section: Introductionmentioning
confidence: 99%